Penyelesaian Sengketa Tanah Terindikasi Overlapping Dengan Cara Mediasi Oleh Badan Pertanahan Nasional (Study Kasus Di Kantor Pertanahan Kabupaten Sukoharjo) - SANTOSO, MUHAMMAD BUDI, Nuswardhani, SH, S.U, Darsono SH.,M.Hum (2015)
Land is the source of life for humans. Basically disputes / conflicts caused by land ownership / control ground unbalanced and uneven ground pose problems certificate overlap (overlapping). National Land Agency can resolve a land dispute by promoting justice, namely through consultation with through mediation. This study uses normative juridical descriptive. Using data types secondary and primary data. Data collection techniques used through the study of literature, documentation, and interviews. By using qualitative data analysis. Based on the results of research and discussion, it can be concluded that the Land Office Sukoharjo overlapping indicated to deal with land disputes that occurred in the village of the District Pucangan Kartasura Sukoharjo. Land Office Sukoharjo resolve land disputes indicated a degree of overlapping with through mediation. The results of the mediation made Minutes of Settlement in order to provide legal certainty.